2021
DOI: 10.3390/pathogens10091105
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic COVID-19 Individuals Tend to Establish Relatively Balanced Innate and Adaptive Immune Responses

Abstract: The sharp increase in the proportion of asymptomatic cases and the potential risk of virus transmission have greatly increased the difficulty of controlling the COVID-19 pandemic. The individual immune response is closely associated with clinical outcomes and pathogenic mechanisms of COVID-19. However, the clinical characteristics and immunophenotyping features of immune cells of asymptomatic individuals remain somewhat mysterious. To better understand and predict the disease state and progress, we performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Most individuals mount a sufficient immune response with an acute phase that clears the virus and then resolves normally. In asymptomatic cases, unusually robust inflammation is well-controlled and C reactive protein (CRP) remains within normal range ( Li et al, 2021 ) while an effective immune response is mounted ( Le Bert et al, 2021 ). In symptomatic cases, inflammatory cytokines and CRP rise dramatically and correlate with disease severity, but return to normal within a few months following resolution of infection regardless of COVID-19 severity ( Sonnweber et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most individuals mount a sufficient immune response with an acute phase that clears the virus and then resolves normally. In asymptomatic cases, unusually robust inflammation is well-controlled and C reactive protein (CRP) remains within normal range ( Li et al, 2021 ) while an effective immune response is mounted ( Le Bert et al, 2021 ). In symptomatic cases, inflammatory cytokines and CRP rise dramatically and correlate with disease severity, but return to normal within a few months following resolution of infection regardless of COVID-19 severity ( Sonnweber et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological mechanisms associated with the risk of intracranial hemorrhage in patients with COVID-19 include systemic inflammation, endothelial dysfunction, increased blood-brain barrier permeability, hyperfibrinolysis, and coagulopathy associated with the infection. [4][5][6][20][21][22][23][24] These alterations have mainly been observed and are more pronounced in symptomatic patients with moderate or severe disease, 25 but they have also been described in asymptomatic infections. [26][27][28] This would explain the excess of bleeding complications after revascularization treatment in patients with both S-COVID and AS-COVID.…”
Section: Discussionmentioning
confidence: 99%
“…Potential underlying mechanisms include systemic inflammation, endothelial dysfunction, blood-brain barrier permeability, hyperfibrinolysis, and infection-associated coagulopathy, which as the authors point out have mostly been observed in moderate or severe disease but have also been reported in asymptomatic infections. [12][13][14] These are considerations that are quite different from typical intercurrent infections and do imply that there may be COVID-specific factors at play.…”
Section: See Related Article P 78mentioning
confidence: 99%